The Behavior of Firms in Financial Distress: Discussion - Altman, Edward I. (Journal of Finance, 1983)
Edward I. Altman, The Behavior of Firms in Financial Distress: Discussion, The Journal of Finance, Vol. 38, No. 2, Papers and Proceedings Forty-First Annual Meeting American Finance Association New York, N.Y. December 28-30, 1982 (May, 1983), pp. 517-522